The Development of A Diagnostic Reading Test of English for the Students of Medical Faculty, Brawijaya University - lndah Winarni (TEFLIN, 2003)
Abstract: This paper describes the development of a diagnostic test of multiple choice reading comprehension as an initial stage in developÂing teaching materials for medical students learning English. Sample texts were collected from all the departments in the faculty. Selection of relevant texts involved the participation of some subject lecturers. Sixty one items were developed from fifteen texts to be reduced to forty items after pilot testing. Face validity was improved. The main trial was carried out to twenty nine students and item analysis was carÂried out. The test showed low level of concurrent validity and the inÂternal consistency showed a moderate level of reliability. The low level of concurrent validity was suspected to result from the test being too difficult for the testees as the item analysis had revealed